Psychometric performance of the Chichewa versions of the EQ-5D-Y-3L and EQ-5D-Y-5L among healthy and sick children and adolescents in Malawi - Lucky G. Ngwira; Hendramoorthy Maheswaran; Janine Verstraete; Stavros Petrou; Louis Niessen; Sarah C. Smith (SpringerOpen, 2023)
Abstract Objectives The EuroQol Group has developed an extended version of the EQ-5D-Y-3L with five response levels for each of its five dimensions (EQ-5D-Y-5L). The psychometric performance has been reported in several studies for the EQ-5D-Y-3L but not for the EQ-5D-Y-5L. This study aimed to psychometrically evaluate the EQ-5D-Y-3L and EQ-5D-Y-5L Chichewa (Malawi) versions. Methods The EQ-5D-Y-3L, EQ-5D-Y-5L and PedsQL™ 4.0 Chichewa versions were administered to children and adolescents aged 8-17 years in Blantyre, Malawi. Both of the EQ-5D-Y versions were evaluated for missing data, floor/ceiling effects, and validity (convergent, discriminant, known-group and empirical). Results A total of 289 participants (95 healthy, and 194 chronic and acute) self-completed the questionnaires. There was little problem with missing data (< 5%) except in children aged 8-12 years particularly for the EQ-5D-Y-5L. Ceiling effects was generally reduced in moving from the EQ-5D-Y-3L to the EQ-5D-Y-5L. For both EQ-5D-Y-3L and EQ-5D-Y-5L, convergent validity tested with PedsQL™ 4.0 was found to be satisfactory (correlation ≥ 0.4) at scale level but mixed at dimension /sub-scale level. There was evidence of discriminant validity (p > 0.05) with respect to gender and age, but not for school grade (p < 0.05). For empirical validity, the EQ-5D-Y-5L was 31-91% less efficient than the EQ-5D-Y-3L at detecting differences in health status using external measures. Conclusions Both versions of the EQ-5D-Y-3L and EQ-5D-Y-5L had issues with missing data in younger children. Convergent validity, discriminant validity with respect to gender and age, and known-group validity of either measures were also met for use among children and adolescents in this population, although with some limitations (discriminant validity by grade and empirical validity). The EQ-5D-Y-3L seems particularly suited for use in younger children (8-12 years) and the EQ-5D-Y-5L in adolescents (13-17 years). However, further psychometric testing is required for test re-test reliability and responsiveness that could not be carried out in this study due to COVID-19 restrictions.